On the strong matrix summability of derived Fourier series - K. N. Mishra; R. S. L. Srivastava (International Journal of Mathematics and Mathematical Sciences)
Strong summability with respect to a triangular matrix has been defined and applied to derived Fourier series yielding a result which extends some known results under a general criterion